2023
DOI: 10.2147/idr.s392585
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Characteristics and Associated Factors for Infection and in-Hospital Mortality in Inpatients with Polymyositis/Dermatomyositis in China: A Retrospective Study

Abstract: Purpose To investigate the clinical features of infection, and associated factor for in-hospital mortality in a southern Chinese cohort with polymyositis/dermatomyositis (PM/DM). Patients and Methods Clinical data were retrospectively reviewed from 2015 to 2022 from a tertiary hospital in southern China. Associated factors for infection and in-hospital mortality were analyzed by multivariate logistic regression analysis. Results A total of 55… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Patients No. Infections Mean Age Male % Study CMV Anti-MDA5/ ARS/TIF1γDM 33 7 At diagnosis 55.9 36.3% R Kazuki 2020 37 PM/DM 2270 18 In years 47.8 33.5% Cohort study Chung 2019 29 Anti-MDA-5 + DM-ILD 42 28 In years 54.8 29.5% P Tsuji 2020 34 IMM 204 3 R Redondo 2018 16 DM/PM 554 24 In years 49.2 36.3% R Lao 2023 12 CMV pneumonitis PM/DM-ILD 25 1 In years 55.4 24.0% Clinical trial Kazuki 2019 32 Herpes-zoster Anti-MDA5/ARS/TIF1γ + DM 33 5 At diagnosis 55.9 36.3% R Kazuki 2020 37 PM/DM-ILD 25 …”
Section: Discussionmentioning
confidence: 99%
“…Patients No. Infections Mean Age Male % Study CMV Anti-MDA5/ ARS/TIF1γDM 33 7 At diagnosis 55.9 36.3% R Kazuki 2020 37 PM/DM 2270 18 In years 47.8 33.5% Cohort study Chung 2019 29 Anti-MDA-5 + DM-ILD 42 28 In years 54.8 29.5% P Tsuji 2020 34 IMM 204 3 R Redondo 2018 16 DM/PM 554 24 In years 49.2 36.3% R Lao 2023 12 CMV pneumonitis PM/DM-ILD 25 1 In years 55.4 24.0% Clinical trial Kazuki 2019 32 Herpes-zoster Anti-MDA5/ARS/TIF1γ + DM 33 5 At diagnosis 55.9 36.3% R Kazuki 2020 37 PM/DM-ILD 25 …”
Section: Discussionmentioning
confidence: 99%
“…Due to a variety of factors such as the characteristics of the disease itself, hormones and immunosuppressants, patients with IIM are highly susceptible to coinfections. According to relevant studies, the incidence of infection in IIM patients is about 27.6%-35.6%, with the lungs being the most common site of infection (66.5%) [1][2]. The occurrence of infections has many disadvantages for patients with IIM, such as hindering the treatment of the disease, causing rapid deterioration of the patient's condition, and several studies have shown that infections are the main cause of death in patients with IIM [3][4].…”
Section: Introductionmentioning
confidence: 99%